Postmarketing adverse events associated with onasemnogene abeparvovec: a real-world pharmacovigilance study - Tianyu Chen; Qiying Chen; Jingfang Ye; Yuzhu Wu; Ting Liu; Yuezhen Zhang (Orphanet Journal of Rare Diseases)
Abstract Background Onasemnogene abeparvovec (OA) is an adeno-associated virus vector-based gene therapy indicated for the treatment of paediatric patients with spinal muscular atrophy(SMA) with biallelic mutations in the survival motor neuron 1 (SMN1) gene. This study focused on analysis of the postmarketing adverse events(AEs) of onasemnogene abeparvovec (OA) reported in the US Food and Drug Administration public data open project (openFDA) database to assess the safety of OA in the real world and to provide a reference for the rational use of this drug in the clinic. Results In total, 1,959 AEs were reported with “onasemnogene abeparvovec” as the primary suspected drug. The top 5 most frequent AEs were pyrexia (461 cases), vomiting (434 cases), aspartate aminotransferase increase (284 cases), alanine aminotransferase increase (260 cases), and hepatic enzyme increase (237 cases). A total of 77 alert signals were generated, 60 of which were not included in the drug label. The top 5 signals included troponin I increase ( ROR of 895.21, 95% CI: 734.43-1091.18), troponin T increase ( ROR of 313.30, 95% CI:220.85-444.44), rhinovirus infection ( ROR of 175.80, 95% CI:130.86-236.17), troponin increase ( ROR of 143.49, 95% CI:114.96–179.10), and increased bronchial secretion ( ROR of 142.71, 95% CI:96.63-210.77). Further analysis of AEs associated with gender and age differences identified 14 high-risk signals related to gender and 10 high-risk signals related to age. Female patients should be vigilant for vomiting, thrombotic microangiopathy, increased troponin T, proteinuria, haematuria, haemolytic anaemia, urinary tract infection, generalised oedema, and atypical haemolytic uraemic syndrome. Male patients should be alert to increased hepatic enzyme, increased bronchial secretion, respiratory tract infection, pallor, and increased blood creatine phosphokinase MB. Patients under 2 years of age should be vigilant for lethargy, increased monocyte count, decreased blood creatinine, and decreased neutrophil count. Patients over 2 years of age should be alert to hypertension, haematuria, rhinovirus infection, increased blood creatine phosphokinase, headache, and malaise. Conclusions Mining of OA alert signals using the openFDA database provides supplementary information on AEs not included in the drug label. Clinical attention should be focused on common, strong-signal, and label-unmentioned AEs to optimise medication regimens and control risks in clinical use.